Influence of Hysteresis on the Vibration Control of a Smart Beam with a Piezoelectric Actuator by the Bouc–Wen Model - Ting Zhang (Shock and Vibration)
The hysteresis property in a smart structure has attracted much attention from researchers for several decades. Hysteresis not only affects the response precision of the smart structure but also threatens the stability of the system. This paper focuses on how the hysteresis property influences the control effect of vibration suppression for a smart beam. Furthermore, the Bouc–Wen model is adopted to describe the hysteresis property of a smart beam and the hysteresis parameters of the hysteresis model are identified with a genetic algorithm. Based on the identification results, the hysteresis model is validated to represent the hysteresis property of the smart beam. Based on the hysteresis model, model reference adaptive control is designed to explore the influence of hysteresis on the vibration control of the smart beam. With some simulations and experiments, it is found that the vibration control effect is influenced when the hysteresis item changes. The vibration control effect will be improved when the hysteresis coefficient in the Bouc–Wen model, as the expected objective model of the adaptive reference model, is within a proper numerical range where the control system is stable. Furthermore, when the time delay is considered in the closed-loop control system, the principle of the hysteresis influence is different. The results indicate that the hysteresis property affects not only the control effect but also the stability of the control system for a smart cantilever beam.